Organizational and individual factors impact on knowledge sharing practice: The association with cost reduction - Ali, A.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Knowledge is considered as the most important asset in organizations. Therefore, knowledge sharing has become the key to organization survival and superior competitive advantage. This study investigates organizational and individual factors influence on knowledge sharing practice. In addition, the study also examines the impact of the knowledge sharing practice on cost reduction. The organizational factors included are management support, organization structure and culture, while individual factors represented through intention, trust, and reciprocity. Accordingly the research model and hypotheses were formulated based on the objective of the study. The primary data were collected from oil and gas industry using online questionnaire as instrument. In fact, all questionnaire items were tested in terms of their reliability using Cronbach's Alpha method. Regression analysis was conducted to test the hypotheses and investigate all the relationships depicted in the model of the study. The results confirmed that all the factors included in the model have a significant relationship with knowledge sharing practice. On the other hand, it is established by the study that the knowledge sharing practice has a positive relationship with the cost reduction. Â© 2016 IEEE.